2010
DOI: 10.1016/j.joca.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical effects of the cannabinoid CB2 receptor agonist GW405833 on rat osteoarthritic knee joint pain

Abstract: These data indicate that GW405833 reduces the mechanosensitivity of afferent nerve fibres in control joints but causes nociceptive responses in OA joints. The observed pro-nociceptive effect of GW405833 appears to involve TRPV1 receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 47 publications
(26 reference statements)
7
59
0
3
Order By: Relevance
“…Consistent with this speculation, inhibition of NGF by treatment with tanezumab was recently shown to have high analgesic efficacy in OA knees compared with placebo [8]. In the present study, CGRP- and TRPV1-positive cells, which are localized in DRG neurons in monoiodoacetate- (MIA-) treated OA animals [35, 36], were increased in the DRG of STR/Ort compared to C57BL/6J mice, suggesting that the elevation of synovial NGF in STR/Ort mice contributes to peripheral sensitization. However, several studies have shown that human OA chondrocytes also produce NGF by inflammatory cytokines [37, 38].…”
Section: Discussionsupporting
confidence: 79%
“…Consistent with this speculation, inhibition of NGF by treatment with tanezumab was recently shown to have high analgesic efficacy in OA knees compared with placebo [8]. In the present study, CGRP- and TRPV1-positive cells, which are localized in DRG neurons in monoiodoacetate- (MIA-) treated OA animals [35, 36], were increased in the DRG of STR/Ort compared to C57BL/6J mice, suggesting that the elevation of synovial NGF in STR/Ort mice contributes to peripheral sensitization. However, several studies have shown that human OA chondrocytes also produce NGF by inflammatory cytokines [37, 38].…”
Section: Discussionsupporting
confidence: 79%
“…(ii) TRPV1 is co-localized with CB1 and CB2 in cerebromicrovascular endothelial cells [62] and with CB1 in endothelial cells from mesenteric arteries of cirrhotic rats [63,64]; (iii) TRPV1 is co-localized with both CB1 and CB2 in mouse bone-marrowderived dendritic cells [65], and in human skeletal muscle cells [66], myometrial smooth muscle cells [67], osteoclasts [68], proximal tubular (HK2) cells of the kidney [69], keratinocytes [70,71], melanocytes [72] and dental pulp cells [73]; (iv) TRPV1 is co-localized only with CB1 in human sperm cells [74], and only with CB2 in synoviocytes from rats after intraarticular injection of mono-iodo-acetate, a model of osteoarthritis [75]. In view of the previously reported cross-talk between TRPV1 and CB1 receptors at the level of down-stream signalling events [76,77], these many examples of co-expression between the channel and one or both cannabinoid receptor sub-types offer the opportunity of widening further the range of pharmacological effects that endogenous mediators capable of activating both types of receptors may have, and, hence, the extent of 'plasticity' that their action can produce in a large variety of biological systems.…”
Section: Co-expression Of Cb1 or Cb2 Receptors And Trpv1 Channels In mentioning
confidence: 99%
“…In patients with osteoarthritis, TRPV1 is expressed on synovium, as well as synovial fibroblasts suggesting both a neuronal and a non-neuronal role of TRPV1 in this condition [9,40]. In rats, TRPV1 is expressed in DRG neurons and knee joint synoviocytes [41,42]. Additionally, in the mono-iodoacetate (MIA) model of osteoarthritis, joint afferents in the DRG, as determined by Fast Blue staining, expressed a greater amount of TRPV1 (72%) compared to normal joint afferents (54%) [40].…”
Section: Expression Changes In Trpv1 Channels In Chronic Pain Condmentioning
confidence: 99%
“… [74] mouseSTZSTZ has direct action on neurons, which up-regulates TRPV1 expression and increases capsaicin-induced currents [14] humanCPPTRPV1 expression was 7-fold higher in pelvic tissues from patients with CPP compared to controls, which was not due to an increase in neuronal fibers. [33] mousePSNLIn neonatal capsaicin-treated mice, TRPV1 expression is absent but increases in A-fiber DRG neurons after PSNL [46] humanOATRPV1 mRNA is increased 5-fold in osteoclasts from osteoporotic and osteoporotic women compared to normal menopausal women. Capsaicin was less potent and produced a decreased Ca 2+ response in osteoclasts from osteoporotic and osteoporotic women compared to normal menopausal women. [42] ratMIATRPV1 is expressed in DRG neurons and knee joint synovium of control and MIA-treated rats. No quantitative differences between groups evaluated. [13] humanGERDTRPV1 mRNA and protein were significantly increased in patients with erosive esophagitis compared to asymptomatic and healthy control patients. [35] mouseSNLInjury increased the percentage of heat sensitive small-diameter IB4 positive isolated DRG neurons (13% control vs. 56% SNL) and conversely decreased the percentage of heat sensitive small-diameter IB4 negative isolated DRG neurons (66% control vs. 34% SNL).…”
Section: Tablementioning
confidence: 99%